Sui Generis Intellectual Property Law Reform: Issues for Australia - Richardson, Megan (Victoria University of Wellington Law Review, 2001)
This article begins by describing the current range of intellectual property rights in Australia (statutory and common law/equity), then canvasses recent reforms that seek to address some of the problems raised by new innovation practices. A particular focus of the article is the piecemeal nature of the law reform process which continues to treat the law in this area in a highly compartmentalised fashion. Some tentative proposals for improvement are made at the end.